"We Are in This Together": Common Group Identity Predicts Majority Members' Active Acculturation Efforts to Integrate Immigrants. (October 2015) - Kunst, Jonas R.; Thomsen, Lotte; Sam, David L.; Berry, John W.
Although integration involves a process of mutual accommodation, the role of majority groups is often downplayed to passive tolerance, leaving immigrants with the sole responsibility for active integration. However, we show that common group identity can actively involve majority members in this process across five studies. Study 1 showed that common identity positively predicted support of integration efforts; Studies 2 and 3 extended these findings, showing that it also predicted real behavior such as monetary donations and volunteering. A decrease in modern racism mediated the relations across these studies, and Studies 4 and 5 further demonstrated that it indeed mediated these effects over and above acculturation expectations and color-blindness, which somewhat compromised integration efforts. Moreover, the last two studies also demonstrated that common, but not dual, groups motivated integration efforts. Common identity appears crucial for securing majorities' altruistic efforts to integrate immigrants and, thus, for achieving functional multiculturalism.